Proposal of methodology for spatial analysis applied to human development index in water basins - Sales, Jomil Costa Abreu [UNESP] (2018)
Historically, the Human Development Index (HDI) is used to measure the socioeconomic performance of a population. Despite harsh criticism about its efficiency as an indicator of development, it is still widely used as a tool for public management planning. This study proposes a methodology using geoprocessing techniques to perform the mapping and prediction of HDI spatial distribution in the Una River Basin (HDIURB). We used data from the 2010 Demographic Census to calculate the sub-indexes of population longevity, education and income. After obtaining the results, we applied Ordinary Kriging geostatistical interpolation to obtain the continuous variation of HDI values. According to the results, the highest value of HDIURB was obtained in the northern region of the basin located near the urban area of the municipality of Ibiúna (0.86), decreasing as it approached the southern region (0.69), classified as an average human development. Finally, the methodology, despite some limitations, proved to be satisfactory, since it was able to represent internal differences in a water basin from the point of view of quality of life of the population. It may be applied as a tool for management and public administration.